High Persister Mutants in Mycobacterium tuberculosis. - Heather L Torrey; Iris Keren; Laura E Via; Jong Seok Lee; Kim Lewis (PLoS ONE, 2016)
Mycobacterium tuberculosis forms drug-tolerant persister cells that are the probable cause of its recalcitrance to antibiotic therapy. While genetically identical to the rest of the population, persisters are dormant, which protects them from killing by bactericidal antibiotics. The mechanism of persister formation in M. tuberculosis is not well understood. In this study, we selected for high persister (hip) mutants and characterized them by whole genome sequencing and transcriptome analysis. In parallel, we identified and characterized clinical isolates that naturally produce high levels of persisters. We compared the hip mutants obtained in vitro with clinical isolates to identify candidate persister genes. Genes involved in lipid biosynthesis, carbon metabolism, toxin-antitoxin systems, and transcriptional regulators were among those identified. We also found that clinical hip isolates exhibited greater ex vivo survival than the low persister isolates. Our data suggest that M. tuberculosis persister formation involves multiple pathways, and hip mutants may contribute to the recalcitrance of the infection.